Optimization of Baku-Sumqayit Passenger Train - Aslanov, Vusal (ADA University, 2019)
Today urbanization and globalization has become a constant process, which has a huge impact on the lifestyle of people. According to the modern research, more that 50 % of worlds’ population live in cities and by 2030, 6 out of 10 people will live in cities. Growth of population, popularity of tourism, globalization trends, work preferences and many other factors tremendously increase transportation needs. People choose public transport for long and short distances, and, since modern life style promote “time is money” slogan, people prefer transport which is fast, comfortable, safe along with the ability to combine travel with work. All these options are offered by public railway transport. Railway is one of the most ancient and popular transport system in the world, efficiently used both for cargo and public transportation, and despite all evident benefits of airplanes for Transocean routes and very long distances, railway keeps strong positions due to lower price and no need for long registration process and necessity to loose extra 2 hours in the airport. In this Research Paper I have chosen the topic of passenger railway transportation efficiency increase due to several reasons. First, I myself work in ADY- a national freight and passenger transportation services provider in Azerbaijan, being one of the largest State-owned entities (SOEs) with the sole shareholder – The Government of Azerbaijan. Second, nowadays Azerbaijan lives the stable population growth, urbanization and needs the better development of infrastructure, where public transport is an integral part. Finally, I assume that since Governments become more conscious about environment, there should be projects on the increase of level of population awareness about ecology, and obviously, electrified railway is more preferable than diesel and gasoline vehicles, polluting atmosphere, creating traffic jams, and carrying less amounts of passengers. In this Paper I have focused on the most popular passenger route - Baku-Sumgayit-Baku, which was launched in 2015, so I could gather more than 3 years data on its usage. For the aims of this Research I have used such analytical tools as SWOT analysis, PEST and Porter’s Five Forces, in order to be able to evaluate internal and external factors of public railway transportation in Azerbaijan, as well as the potential and weaknesses of ADY itself. Also, I have developed my proposals for efficiency increase, such as developing new pricing strategy and new transport schedule, which will serve better for the passengers, based on the analysis of alternative methods of transportation and Survey results. The results of my analysis have been set up in the form of recommendations to this BCP.
Keywords: Business; Railroads.; Transportation.; Transportation -- Azerbaijan.